Vectorcardiographic diagnostic & prognostic information derived from the 12‐lead electrocardiogram: Historical review and clinical perspective - Man, Sumche; Maan, Arie C.; Schalij, Martin J.; Swenne, Cees A. (Journal of electrocardiology, 2015)
In the course of time, electrocardiography has assumed several modalities with varying electrode numbers, electrode positions and lead systems. 12-lead electrocardiography and 3-lead vectorcardiography have become particularly popular. These modalities developed in parallel through the mid-twentieth century. In the same time interval, the physical concepts underlying electrocardiography were defined and worked out. In particular, the vector concept (heart vector, lead vector, volume conductor) appeared to be essential to understanding the manifestations of electrical heart activity, both in the 12-lead electrocardiogram (ECG) and in the 3-lead vectorcardiogram (VCG). Not universally appreciated in the clinic, the vectorcardiogram, and with it the vector concept, went out of use. A revival of vectorcardiography started in the 90’s, when VCGs were mathematically synthesized from standard 12-lead ECGs. This facilitated combined electrocardiography and vectorcardiography without the need for a special recording system. This paper gives an overview of these historical developments, elaborates on the vector concept and seeks to define where VCG analysis/interpretation can add diagnostic/prognostic value to conventional 12-lead ECG analysis. •Historical overview of the development of electrocardiography and vectorcardiography•Origin and evolution of the heart vector and lead vector concepts•Decline and revival of vectorcardiography•Vectorcardiography as an extension of the standard 12-lead electrocardiogram•Current and future clinical and research applications of the vectorcardiogram